A simple procedure for the preparation of laponite and thermoplastic starch nanocomposites: Structural, mechanical, and thermal characterizations - Aouada, Fauze A. [UNESP]; Mattoso, Luiz H.C.; Longo, Elson [UNESP] (SAGE Publications, 2013)
The aim of this article is to propose advances for the preparation of hybrid nanocomposites prepared by the combination of intercalation from solution and melt-processing methods. This research investigates the effect of the laponite RDS content on the thermal, structural, and mechanical properties of thermoplastic starch (TPS). X-ray diffraction was performed to investigate the dispersion of the laponite RDS layers into the TPS matrix. The results show good nanodispersion, intercalation, and exfoliation of the clay platelets, indicating that these composites are true nanocomposites. The presence of laponite RDS also improves the thermal stability and mechanical properties of the TPSmatrix due to its reinforcement effect which was optimized by the high degree of exfoliation of the clay. Thus, these results indicate that the exfoliated TPS-laponite nanocomposites have great potential for industrial applications and, more specifically, in the packaging field. © The Author(s) 2011 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Keywords: Clay; mechanical properties; nanocomposites; reinforcement; thermal properties; X-ray; Clay platelets; Hybrid nanocomposites; Laponites; Melt processing; Nano-dispersions; Reinforcement effects; Thermal characterization; Thermoplastic starch; Industrial applications; Mechanical properties; Reinforced plastics; Reinforcement; Starch; Thermodynamic properties; X ray diffraction; X rays; Nanocomposites